Novel microsatellite markers discovery in Patagonian toothfish (Dissostichus eleginoides) using high-throughput sequencing - Killen Ko Garcia; Jorge Touma; Scarleth Bravo; Francisco Leiva; Luis Vargas-Chacoff; Ariel Valenzuela; Patricio Datagnan; Rodolfo Amthauer; Alberto Reyes; Rodrigo Vidal (Molecular Biology Reports, 2019)

Early life stage bottlenecks of carnivorous molluscs under captivity: a challenge for their farming and contribution to seafood production - Iker Uriarte; Marcela Astorga; Juan Carlos Navarro; María Teresa Viana; Carlos Rosas; Carlos Molinet; Jorge Hernández; Jorge Navarro; Ignacio Moreno‐Villoslada; Rodolfo Amthauer; Gudrun Kausel; Jaime Figueroa; et al. (Reviews in Aquaculture, 2019)
This work brings together the view of different specialists in the areas of larviculture, physiology, ecology, nutrition and animal health, regarding how to deal with the aquaculture farming of species with complex life cycles in a multidisciplinary way, using as models the octopus and the muricid C. concholepas , with the aim of reducing the gap between the experimental and the industrial culture of species that are relevant for the diversification of aquaculture, particularly in Chile. Although these species are similar in their difficulty to reach the terminal planktonic phase prior to juvenile, they differ in the bottlenecks they have to overcome to reach it. Relevant aspects of study to achieve juvenile production from early life stages rearing, whether for repopulation or for ongrowing, are as follows: (i) Replacement or supplementation of live diets with inert diets to achieve significant survival values over the first stages of life. (ii) Physiological approaches to establish cultivation conditions evaluating the individual responses to several rearing conditions, specially the interaction between temperature, dissolved oxygen and acidity. Studies of urgent character due to the global warming scenario. (iii) Genomic studies associated with the effect of ontogenetic development, environment, health and nutrition on gene expression to understand, in an integrated way, the key processes for the development and growth of immature stages. (iv) Studies on the control of reproduction, the quality control of the ova, the genetic structure of reproductive populations and the characterization of diseases are also necessary to achieve efficient hatchery technologies.